Energy Priority With Link Aware Mechanism For On-Demand Multipath Routing In Manets - P. Anusha, Aala Ravikiran, V. Lakshman Narayana, Venkata Rao Maddumala (International Journal of Advanced Science and Technology, 2020)
Mobile Ad Hoc Networks (MANETs) are multi-hop wireless networks where all nodes cooperatively maintain network connectivity. When the size of the network is large and the nodes are highly mobile, the frequency of link failure and energy consumption of the nodes will be more. Link aware will be identified only during the transmission of data packets. Due to this, control load of the network will increase. To overcome this problem, In This paper focuses on link quality between nodes in an ad hoc network in emergency scenarios through the design of the Energy Priority and Link Aware Ad-hoc On-demand Distance Multipath Vector (EPLAOMDV) routing protocol. EPLAODV improves the link quality between nodes through SNR. For performance analysis, the NS2.35 network simulator was used. Simulation time and traffic load were the major simulation parameters. From the simulation results, it is observed that EPLAOMDV performs better than EPLAODV. We applied this integrated mechanism on Ad hoc On-demand Multipath Distance Vector (AOMDV) routing protocol to make it as Energy Priority Link Aware AOMDV (EPLAOMDV) routing protocol. The performance of EPLAOMDV is also compared with that of standard EPLAODV with the help of simulations carried out using Ns2 simulator. From simulation results it is learnt that EPLAOMDV decreases the number of control packets, increases the packet delivery ratio and reduces power consumption.